Bicycle and pedestrian studies based on data from national household travel survey - Edwards, Stephen; Ivey, Stephanie; Lipinski, Martin; Golias, Mihalis (My University, 2012)
Communities around the nation are addressing new federal regulations and an increased pressure by national and local advocacy groups to accommodate bicyclists and pedestrians in transportation projects. To meet these demands, state and local transportation planning agencies must often rely on data sets derived from small samples and with little previous application to develop user characteristics and travel demand models that estimate the effect an increase in bicycle and pedestrian infrastructure will have on the transportation network. One of the main sources for data on travel and transportation available to industry professionals is the National Household Travel Survey (NHTS), which FHWA conducts every 5 to 7 years and which provides data sets on daily travel for all transportation modes, including information on driver characteristics, travel time, trip purpose, time of day, and day of the week a trip took place. An add-on program with NHTS offers agencies an opportunity to obtain local data that may be used for bicycle and pedestrian studies. This paper presents the results of a literature review on the current methodology NHTS uses to gather bicycle and pedestrian data, the application of the data by transportation planning agencies and researchers, and lessons learned in the use of those data for bicycle-pedestrian studies.